(untitled) - Lawhead, James B. (Australia, 2005)
This completely up-to-date resource is a must have for individuals raising livestock, caring for companion animals, new veterinarian technicians, or anyone who wants to learn more about veterinary medicine. Practical application of the material is backed by a description of clinical significance, and new content on current topics such as avian influenza has been added. The updated career section reflects the changing needs of veterinary professionals
Keywords: Vetarinary medicine